Induction of apoptosis in S180 tumour bearing mice by polysaccharide from Lentinus edodes via mitochondria apoptotic pathway - Yu Zhang; Qiang Li; Yamin Shu; Hongjing Wang; Ziming Zheng; Jinglin Wang; Kaiping Wang (Journal of Functional Foods, 2015)
JLNT, a purified polysaccharide with the structure of β-(1→3)-D-glucose main chains and β-(1→6)-D-glucose side chains and with an average molecular weight of 605.4 kDa, was extracted and isolated from the fruitbodies of Lentinus edodes, which has immunoregulatory activity and anti-tumour effects. In the present study, we found that JLNT possessed direct anti-tumour effects on MCF-7 and S180 cells and apoptosis -inducing activity in S180 tumour bearing mice. Therefore, we investigated the mechanisms of JLNT-induced apoptosis. Results showed that JLNT increased the expression of p53, enhanced the Bax/Bcl-2 ratios by up-regulating Bax and down-regulating Bcl-2, promoted the expression of Smac, leading to the activation of caspase-3 and finally the initiation of cell apoptosis in S180 tumour bearing mice. Taken together, these findings provide the experimental evidence that JLNT could induce apoptosis of S180 cells via mitochondria pathways.